Entering an ambiguous space: Evoking polyvocality in educational research through collective poetic inquiry - Kathleen Pithouse-Morgan; Inbanathan Naicker; Vitallis Chikoko; Daisy Pillay; Pholoho Morojele; Teboho Hlao (Perspectives in Education, 2014)
We explore how the participatory, literary arts-based methodology of collective poetic inquiry can facilitate awareness of, and insight into polyvocality in educational research. Using found poetry and haiku poetry, we present a poetic performance in which we engage with diverse voices that manifest in multiple data sources: a student participant’s photographic collage and unstructured interview transcript; audiorecorded discussions with research team members and a conference audience, and research team members’ written reflections. We aim to contribute to methodological conversations about poetry as research, with a particular focus on understanding more about the potential of collective poetic inquiry for evoking polyvocality in educational research. Drawing on notions of ‘un-knowing’, ‘not-knowing’ and ‘productive ambiguity’, we conceptualise our participatory research process as polyvocal and invite readers to join us in considering how cultivating polyvocality in educational research might bring about change in ourselves and in our ways of knowing as members of research communities. The article highlights our evolving understanding that how we research shapes and reshapes what we come to know and un-know and how we communicate that knowing.